Automotive battery pack standards and design characteristics: a review - Saeid Haghbin; Morteza Rezaei Larijani; MohammadReza Zolghadri; Shahin Hedayati Kia (Discover Applied Sciences)
Abstract The latest advancements and near-future trends in automotive battery packs, underlying regulatory compliance, and performance requirements are presented in this paper. In response to these specifications, high-level solutions that converge towards a standard architecture for passenger cars are provided. Transitioning to high-voltage systems (400 V–800 V), which support charging power levels above 350kW, reduces the required current. This, in turn, lowers the weight and volume of cell/module connectors and high-voltage cables in the drivetrain. Additionally, optimization strategies are crucial for enabling fast charging in all conditions, especially in cold climates, while ensuring safe operation, preventing thermal runaway, and reducing charging times to under 20 minutes. Also, advances in energy density (up to 300 Wh/kg) and battery capacities make advancements in enhancing the electric vehicle’s range beyond 1000 km per charge. Key factors such as electrical performance, safety, mechanical integrity, reliability, endurance, environmental conditions, and diagnostics are examined. This study explores the next generation of cost-effective and high-performance battery systems and discovers near-future battery technologies, including sodium-ion chemistry and rare-earth-free alternatives, as well as battery applications in aviation.